2009
DOI: 10.1038/hr.2009.80
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an L- and N-type calcium channel blocker in hypertensive patients with neurovascular compression of the rostral ventrolateral medulla

Abstract: The rostral ventrolateral medulla is an important regulation center of sympathetic nerve activity. Several clinical studies have indicated a possible association between essential hypertension and neurovascular compression of the rostral ventrolateral medulla. We have found that patients with essential hypertension and neurovascular compression of the rostral ventrolateral medulla by adjacent arteries have increased sympathetic nerve activity and that microvascular decompression of the rostral ventrolateral me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Another study showed that in hypertensive patients with neurovascular compression of the rostral ventro-lateral medulla (increased sympathetic nerve activity), Cilnidipine reduces left ventricular mass [44], these two studies are corroborative with present study. A significant reduction in left ventricular mass index with relatively short course of Amlodipine [45], in the patients with concentric LVH, Amlodipine treatment produced significant regression in hypertrophy [46], as well as Amlodipine caused significant reduction in LV Mass and RWT coincides with present study [47].…”
Section: Discussionsupporting
confidence: 80%
“…Another study showed that in hypertensive patients with neurovascular compression of the rostral ventro-lateral medulla (increased sympathetic nerve activity), Cilnidipine reduces left ventricular mass [44], these two studies are corroborative with present study. A significant reduction in left ventricular mass index with relatively short course of Amlodipine [45], in the patients with concentric LVH, Amlodipine treatment produced significant regression in hypertrophy [46], as well as Amlodipine caused significant reduction in LV Mass and RWT coincides with present study [47].…”
Section: Discussionsupporting
confidence: 80%
“…We have found that cilnidipine, a calcium Efficacy of clonidine in hypertension T Sakuma et al channel antagonist that blocks not only L-type channels but also Ntype channels and inhibits SNA by inhibiting the release of NE from the peripheral sympathetic nerve endings, reduces BP and plasma NE more significantly in untreated EH with NVC than in those without NVC of RVLM. 30 Accordingly, it is possible that any antihypertensive agent that reduces SNA activity may decrease BP especially in hypertensive patients with NVC of RVLM. To test this hypothesis, clinical studies examining the effects of other sympatholytic agents such as a-blockers and b-blockers are also needed, and if this hypothesis is confirmed, it will become necessary to evaluate hypertensive patients for the presence of NVC of RVLM before deciding the treatment for hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Morimoto et al [26][27][28] and Aota et al 2 found in their studies that patients with essential AH and NC of the RVLM have increased sympathetic nerve activity and that MVD of the RVLM normalizes blood pressure and sympathetic nerve activity. Sympatholytic agents decreased blood pressure significantly more in hypertensive patients with RVLM compression than in hypertensive patients without RVLM compression.…”
Section: 36mentioning
confidence: 99%
“…Compression of this center might yield a heightened sympathetic tone, leading to AH. 2,7,12,25,29,35 Jannetta et al [17][18][19] demonstrated that microvascular decompression (MVD) of the RVLM could normalize or improve a raised blood pressure. Because the RVLM is close to the origin of the facial nerve, vessel loops originating from the vertebral/basilar arteries might be responsible for multiple neurovascular compressions (NCs), inducing both hemifacial spasms (HFSs) and AH.…”
Section: 14mentioning
confidence: 99%
See 1 more Smart Citation